STABILITY AND CROP PRODUCTIVITY OF PISTACHIO TO EXTERNAL FACTORS (Academicia Globe: Inderscience Research, 2023)
Pistachio tree in Uzbekistan is naturally distributed in rainfed lands within 400-1200 m above sea level and annually bear fruit. In dry lands, summer period there is a sharp decrease in soil moisture, in consequence of which some phenotypes of pistachio trees are damaged by drought, i.e. 20-80% of the leaves fall off. As a result of this undesirable phenomenon, the processes of photosynthesis and synthesis of organic substances, as well as the harvest of the next year, sharply decrease. Resistant to the summer drought were varieties of "Albina" (productivity 2.0 c/ha), "Mountain Pearl" (2.6 c/ha), forms 518-G and 521-G (1.7 c/ha). These varieties and forms have a high index of resistance to vegetative and generative organ for summer drought.